Bibliometric Analysis of Telemedicine and E-Health Literature - Sikandar, Huma; Vaicondam, Yamunah; Parveen, Shazia; Khan, Nohman; Qureshi, Muhammad Imran (International Journal of Online and Biomedical Engineering (iJOE), 2021)
Emerging technologies such as artificial intelligence, the internet of things, cloud computing, and wearable gadgets have broadened the scope of telemedicine and eHealth in past years. This research aims to investigate the past patterns of telemedicine and eHealth research over the past ten years. Scopus database was used to extract the article information of the selected articles. The research is conducted on 1401 articles in which we investigated the top authors, journals, institutions, countries, and highly cited articles. Our research findings project the growth trend of publications and the pattern of authors and distribution of articles and the core journals. The top 10 authors in the selected field were identified so were the highly cited articles. Co-occurrence analyses of keywords, authors, and countries co-authors analysis and bibliographic coupling of VOS viewer documents were conducted. The limitations and directions for future researchers have also been discussed.